Badanie Modeli Spawanych Wirników przy Skręcaniu, Zginaniu i Ruchu Obrotowym - Wasilczenko, I.P.; Kepcz, T.Ju.; Sawczenko, W.I. (Engineering Transactions, 1972)
Experimental investigations are performed concerning the stress concentration coefficients occurring in welded drum rotors; in the photo-elastic experiments epoxy resin models are used to determine the three-dimensional state of stress. The models are freezed after loading and then small specimens of various orientation are cut out of the model and analyzed in, a polariscope. The concentration of stresses is investigated in the cases when the rotor is subject to bending or to rotary motion. Certain particular results and their analysis are presented in detail.